Technology of Improvement of Professional Training of Future Physical Education Teachers - Akhmedov Gʼolibjon Gʻulomovich (Periodica Journal, 2022)
The article studies the technology of increasing the professional training of future physical education teachers. The possibilities of a practice-oriented technology for the formation of professional competencies of future teachers of physical culture are considered and options for solving the problem of their preparation for the implementation of the main requirements of the State Educational Standards of the Republic of Uzbekistan for the results of training in the subject "Physical Education" are proposed.
Keywords: students; discipline; formation; physical